AUDITING WITH ACCENT ON THE INCOME STATEMENT. - Gopez, Eduardo C. (The Accounting Review, 1954)
Abstract The article focuses on the income statement approach in auditing. It is not a complete abandonment of the audit of the balance sheet but only a shift in the direction of the emphasis. Instead of auditing the balance sheet with the income statement as a by-product, the process is reversed, that is, the income statement should be audited with the balance sheet as a by-product. Much has been written about the income statement. A survey of contemporary accounting literature indicates that this subject is a central feature dominating the writings of practitioners as well as teachers of accounting. Perhaps, this is a belated recognition of the fact that the value of a business is dependent mainly upon its capacity to generate income. But this concern over profits seems to be as old as the art of bookkeeping itself. Even the earliest financial statements of Florentine merchants in the 14th century were used to determine profits of the then flourishing partnerships. In the 16th century, a so-called balancing account was developed, wherein real accounts were closed in a manner similar to the closing of revenue and expense into a profit and loss account.